Análisis de la comunicación interna de la agencia naviera: representaciones marítimas del Ecuador y su impacto en el desarrollo operacional - Dume Velasco, Silvia Leonor (2016)
Nowdays, private and public institutions today not only work to improve their externa communication but also for communication it is maintained between its employees and how this is reflected in their job performance and therefore if there is a good job performance arise problems which need to take corrective action. In the shipping company REMAR S.A., a private company owned by Ultramar Network is headquartered in Chile, currently it has an internal disadvantage on communication handling for their employees. Therefore, this problem is the motivator to conduct research on its communication channels factor, performance, impact on the development of the company and the possibility of creating a public relations department……